Assessing Health System Performance Proof of Concept for a HSPA Dashboard of Key Indicators - Figueras, Josep; Karanikolos, Marina; Guanais, Frederico; Lessof, Suszy (OECD Publishing, 2023)
This report, jointly developed by the European Observatory, OECD, and WHO Europe, serves as a proof of concept for a Health Systems Performance Assessment (HSPA) dashboard. HSPA is pivotal for health system transformation, providing policymakers with key indicators to identify and address system performance issues. This brief represents a step towards more policy-friendly dashboards, emphasizing the need for a focused set of HSPA indicators aligned with policy goals. The brief highlights the alignment and complementarity of the WHO-Observatory global HSPA framework and OECD's renewed framework, which aid policymakers in navigating health systems with actionable, policy-relevant indicators. These frameworks establish connections between performance indicators, health system functions, and overarching goals, supporting a coherent policy dashboard. Tracer indicators, like workforce, digital health, and service delivery outcomes, are emphasized as crucial for assessing key policy areas. The report underscores the importance of investing in data collection and infrastructure at national and international levels to make HSPA effective. It advocates for continuous improvement and collaboration among major international organizations, including WHO, OECD, EU, and the Observatory, to align methodologies and support informed policy decision-making